1994
DOI: 10.1034/j.1600-0501.1994.050410.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of smoking on early implant failure

Abstract: This retrospective study describes the effect of smoking on initial fixture failure before functional loading with fixed prosthetic restorations. Of 208 installed Brånemark fixtures in the mandible, only 1 failed (0.5%), and no detrimental effect of smoking on fixture survival could be detected. In the maxilla, 10/244 fixtures failed (4%); 7/78 fixtures failed in smokers and 3/166 in nonsmokers. The failure rate before loading was 9% in smokers versus 1% in nonsmokers and was statistically significant, despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
142
1
12

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(168 citation statements)
references
References 0 publications
13
142
1
12
Order By: Relevance
“…A meta-analysis of the literature conducted by Papapanou (1996) for the 1996 World Workshop in Periodontics revealed that smokers have an almost 3-fold increase in their risk for severe periodontal disease vs non-smokers. Evidence also indicates that failures of endosseous dental implants (relating to osseointegration) are increased in smokers vs non-smokers (Bain & Moy 1993, De Bruyn & Collaert 1994.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of the literature conducted by Papapanou (1996) for the 1996 World Workshop in Periodontics revealed that smokers have an almost 3-fold increase in their risk for severe periodontal disease vs non-smokers. Evidence also indicates that failures of endosseous dental implants (relating to osseointegration) are increased in smokers vs non-smokers (Bain & Moy 1993, De Bruyn & Collaert 1994.…”
Section: Introductionmentioning
confidence: 99%
“…[15] An added failure rate of about 8% was noticed in smokers that occurred either at the implant exposure or after a short time of implant loading. [16] In this study, the effect of conventional versus Schlosser's techniques during competes denture construction was compared to evaluate the effect of these different approachs on the implant stability and marginal bone loss. Complete dentures fabricated using "Schlosser's Technique" in which the try-in stage is followed by completed construction of upper denture then readjusting occlusion of lower trial denture base against the remounted upper processed denture, and finally, the construction of lower complete.…”
Section: Discussionmentioning
confidence: 99%
“…5 These also compromise the healing process 6 and increase the risk of implant failure. [7][8][9][10][11] It has been suggested that smokers are informed of this risk rather than smoking being seen as a contraindication to implant treatment. 12 All three patients had a history of cigarette smoking and two had high alcohol consumption, and they represented high risk cases for developing oral cancer.…”
Section: Discussionmentioning
confidence: 99%